PENGARUH DEWAN KOMISARIS DAN INVESTMENT ACCOUNT HOLDERS TERHADAP KINERJA BANK SYARIAH DI INDONESIA - Chandra Dwi Setyawan; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2017)
The purpose of this study was to examine the level of performance of Islamic Banks in Indonesia based board direcotrs attributes and Investment Account Holders. Then, this research ensures determinants on the disclosure. Hypothesis testing is based on level bank performance in the Annual Report of Islamic Banks. Using the legitimacy theory, the research examined level bank performance in Islamic Banks based on Islamic principles. Samples were taken from 7 Islamic Banks in Indonesia for 7 years. The study design using multiple regression analysis. The test results showed IAH (Investment Account Holders) significantly with bank performance of Islamic Bank. While that BS as number of board members and the board composition does not significantly with Bank Performance.